Development of quality metrics for ambulatory pediatric cardiology: Chest pain. (27th June 2017) - Lu, Jimmy C.; Bansal, Manish; Behera, Sarina K.; Boris, Jeffrey R.; Cardis, Brian; Hokanson, John S.; Kakavand, Bahram; Jedeikin, Roy
Abstract: Objective: As part of the American College of Cardiology Adult Congenital and Pediatric Cardiology Section effort to develop quality metrics (QMs) for ambulatory pediatric practice, the chest pain subcommittee aimed to develop QMs for evaluation of chest pain. Design: A group of 8 pediatric cardiologists formulated candidate QMs in the areas of history, physical examination, and testing. Consensus candidate QMs were submitted to an expert panel for scoring by the RAND‐UCLA modified Delphi process. Recommended QMs were then available for open comments from all members. Patients: These QMs are intended for use in patients 5–18 years old, referred for initial evaluation of chest pain in an ambulatory pediatric cardiology clinic, with no known history of pediatric or congenital heart disease. Results: A total of 10 candidate QMs were submitted; 2 were rejected by the expert panel, and 5 were removed after the open comment period. The 3 approved QMs included: (1) documentation of family history of cardiomyopathy, early coronary artery disease or sudden death, (2) performance of electrocardiogram in all patients, and (3) performance of an echocardiogram to evaluate coronary arteries in patients with exertional chest pain. Conclusions: Despite practice variation and limited prospective data, 3 QMs were approved, with measurable data points which may be extracted from the medical record. However, further prospective studies are necessary to define practice guidelines and to develop appropriate use criteria in this population.